2003
DOI: 10.1002/cne.10631
|View full text |Cite
|
Sign up to set email alerts
|

Cadherin expression coincides with birth dating patterns in patchy compartments of the developing chicken telencephalon

Abstract: Some gray matter regions of the vertebrate brain, e.g., the mammalian striatum, are organized into clusters of functionally similar neurons ("patches") that are surrounded by a gray matter matrix. A similar type of compartmentation recently has been found also in the avian telencephalon, based on two sorts of evidence. First, a birth dating study showed that, in some telencephalic areas, cells born at the same time form "isochronic" cell clusters, which differ in their birth dating pattern from their surroundi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 44 publications
3
16
0
Order By: Relevance
“…Neurogenesis in the chick dorsal telencephalon occurs between E4 and E9 (Tsai et al 1981a(Tsai et al , 1981b, and isochronic cluster formation has been observed with BrdU delivery during peak neurogenesis (E5-E7) (Heyers et al 2003). By injecting E5 to E9 brains with the routine BrdU dose and collecting brains at E14 for BrdU detection and in situ hybridization, we established that BrdU clusters can be produced from E5 to E8 and are consistently associated with inappropriate EMX1 and DACH2 expression (Fig.…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…Neurogenesis in the chick dorsal telencephalon occurs between E4 and E9 (Tsai et al 1981a(Tsai et al , 1981b, and isochronic cluster formation has been observed with BrdU delivery during peak neurogenesis (E5-E7) (Heyers et al 2003). By injecting E5 to E9 brains with the routine BrdU dose and collecting brains at E14 for BrdU detection and in situ hybridization, we established that BrdU clusters can be produced from E5 to E8 and are consistently associated with inappropriate EMX1 and DACH2 expression (Fig.…”
Section: Resultsmentioning
confidence: 74%
“…On E5 to E9, a small window was cut in the eggshell and 1 to 3 µl BrdU solution was injected into one of the embryo's vitelline veins through a glass micropipette (tip diameters: 20-40 microns) connected to a picospritzer. The 15-mg/ml dose is a "routine" dose similar to that employed in other studies of chick forebrain development (Striedter and Keefer 2000;Redies et al 2002;Heyers et al 2003). In scout experiments, we found that with the 0.15-mg/ml dose, BrdU was not detected over background (n=8 where all failed detection), whereas with the 0.5-mg/ml dose, a BrdU signal could be regularly, but not invariably, detected (n=18 where 2 failed detection) and is referred to in this study as the threshold dose.…”
Section: Brdu Injectionsmentioning
confidence: 99%
“…While this situation persists roughly across stages HH32-36, the MD and MV moieties of the adult mesopallium are not mutually distinguishable. However, the two sorts of postmitotic cells gradually segregate one from the other after stage HH36, possibly because of differential expression of cadherins known to mediate selective homologous adhesivity and consequent aggregative readjustments of cell positions (see Redies et al, 2001Redies et al, , 2002Heyers et al, 2003).…”
Section: The Claustrum Homolog Lies In the Avian Mesopalliummentioning
confidence: 99%
“…The Pcdhs derived from these gene clusters are predominantly expressed in the nervous system and localized to synaptic junctions (4 -6). Functionally connected neurons are often characterized by the expression of a distinct set of cadherins, which may thus provide an adhesive code regulating neuronal differentiation and synaptogenesis (7)(8)(9). The family-specific constant domains of Pcdh␣-and Pcdh␥-proteins could transduce different extracellular informations into a common intracellular signaling pathway or other executive functions.…”
mentioning
confidence: 99%